(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hichem K, Ramzi H, Djemoi M. 2019. Biodiversity and distribution of groundwater fauna in the Oum-El-Bouaghi region (Northeast of Algeria). Biodiversitas 20: 3553-3558. This study concerns the aquatic fauna of wells and springs in north of the city of Oum El Bouaghi, in the western part of the Tamlouka plain, north-eastern Algeria. 16 wells and two springs were selected and a seasonal sampling of the aquatic fauna was carried out from September 2017 to May 2018, covering periods of high and low water. Two types of traps were used: the phreatobiological net and baited traps. The composition of fauna was found to be 26 taxa and 6617 individuals, dominated by Crustaceans 47% followed by insects and shellfish 23% for each. Only one stygoby species was collected mainly: Pseudoniphargus djemoi.